Modeling climate change impact on the hydropower potential of the Bamboi catchment - Bossa, Yaovi Aymar (My University, 2020)
Understanding climate change impacts helps adaptation efforts in the energy sector. This study evaluates the impact of future climate change on the hydropower potential (HPP) of the Bamboi catchment in West Africa combining the HBV-light rainfall-runoff model and a hydropower generation model. Two regional climate simulation datasets MPI-ESM-REMO and WASCAL under RCP 4.5 were applied to the validated HBV light to simulate the catchment discharge. Based on reference and future simulated discharges, a 1.3 MW run-of-river hydropower plant was designed to evaluate the HPP of the catchment. Hydrological and HPP changes were expressed as the difference between two future periods (2020–2049 and 2070–2099) and a reference period (1983–2005). The climate datasets projected a mean annual precipitation increase by 8.8% and 7.3% and discharge increases by 11.4% and 9.735% for the 2020–2049 and 2070–2099 periods, respectively. However, an overall decrease of hydropower generation by − 9.1% and − 8.4% for the 2020–2049 and 2070–2099 periods, respectively, was projected. These results stem from an increase in discharge for the rainy season not convertible into hydropower, combined with a decrease in discharge during the dry months that leads to important HPP losses.
Keywords: Climate change; Hydropower; Run-of-river; Hydrological modelling